"Visa aktning för din far och din mor" - Åsa Bergenheim; Jonas Liliequist (Nordisk Tidsskrift for Kriminalvidenskab)
Today, violent abuse of parents by their grown-up children is veiled in silence; hut this has not always been the case. In 17th and 18th century Sweden, violent and verbal abuse of parents constituted a capital crime, and in the 19th century physical abuse of parents was still regarded as a serious crime. The turning point came in 1864 when parental abuse was excluded from the new penal code as an independent category of crime – a first step on the road to the modern veil of silence. The aim of this article is to analyse today’s silence and violent abuse in the light history. In the long run this was a history of changing attitudes and meanings. While the children of early modern families were obliged by both law and religion to respect their parents as the fundament of society, the rise of the modern bourgeoisie ideology implied that families should be united by bands of love and affection as a natural fact which didn’t need to be regulated by law. What was seen as sin and crime in early modern society was diagnosed as a psychological and social deviation in the emerging modern society.